Spot the difference at the nanoscale: identical location electron microscopy in electrocatalysis - Hodnik, Nejc; Cherevko, Serhiy (Current Opinion in Electrochemistry, 2019)
Identical location electron microscopy (IL-EM) offers a unique opportunity to track the morphological, compositional, and structural changes at the nanoscale in the systems where direct EM visualization is difficult or even currently impossible, for example, aqueous electrochemistry. Since its introduction by Mayrhofer and Arenz et al. in 2008 (Electrochemistry Communications 10 (2008) 1144–1147) to reveal degradation mechanisms in the state-of-the-art Pt/C catalyst in proton exchange membrane fuel cells, numerous electrochemical and nonelectrochemical systems were addressed by IL-EM. Thus, other types of fuel cells, water electrolysis, electrochemical synthesis, batteries, heterogeneous catalysis, and so on were addressed. In this short review, we highlight the most promising IL-EM applications focusing on the very recent studies. Moreover, we discuss the future perspectives of IL-EM, which, we believe, will benefit from the availability of the equipment that enables real atomic resolution and tomography, supported by computer simulations.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Electrocatalysis; Electrolysis; Fuel cells; Microscopy; Stability